SPIRIT PERJUANGAN TUANKU NAN RENCEH DALAM KARYA SENI LUKIS - NONG REFA, Drs. Arisumedi, M.Sn., Drs. Erfizal, M.Pd. (Serupa The Journal of Art Education, 2019)
The goals of the final to visualisation of the fight stuggle of Tuangku Nan Renceh on Painting Art. The use for improve interest to learn the villages histories exspecially is Minangkabau.The result of idea, writer hold many creation about some important think in struggle of Tuanku Nan Renceh. The research this method with get five steps. Prepare, elaboration, syntesis, realitation, concept and settlement. Then get exhibited.The ten of creation presented stories about many important occurance in struggle of Tuanku Nan Renceh, with the tittle as follows Anggapan Kelam, Dilema Sang Pemimpin, Pemimpin Misterius, Suara Jihad, Terstruktur, Gelora Jihad, Lago Sakandang, Simbol Sederhana, Puncak Kejayaan and Harapan.